Production, Purification and Characterization of Bacteriocin Produced by Novel L. Pentosus MW857478 for Enhancement of Food Safety and Shelf-Life of Paneer - Verinder virk; Garima Verma; Chand Ram (Indian Journal of Forensic Medicine & Toxicology, 2021)
This research paper is based upon the production, purification and characterization of bacteriocin byL.pentosusMW857478 followed by its enhancement of food safety and shelf life of paneer. In recentyear LAB (Lactic acid bacteria) produced bacteriocin attract a great attention of researcher due totheir many potential applications. This paper focused on isolation, identification, evaluation of broadspectrum inhibitory activity, production and purification, characterization and evaluation of food safetyand shelf life of paneer. Bcateriocin produced by L. pentosus showed antagonistic activity against foodspoiling pathogens in broad range of Bacteriocin production parameter was optimized with pH 5.5incubated at 35°C for L. pentosus. Bacteriocin was purified by ammonium sulphate precipitation andpurified bacteriocin with single band on SDS-PAGE for molecular weight. The purified bacteriocinstable at 2-10 pH and 30-75°C temperatures, suggesting L. pentosus a potent candidates for safety andextending shelf life of paneer for 15 days.